Proteomics and Comparative Genomic Investigations Reveal Heterogeneity in Evolutionary Rate of Male Reproductive Proteins in Mice (Mus domesticus) - Dean, Matthew D. (Oxford University Press, 2009)
Male reproductive fitness is strongly affected by seminal fluid. In addition to interacting with the female environment, seminal fluid mediates important physiological characteristics of sperm, including capacitation and motility. In mammals, the male reproductive tract shows a striking degree of compartmentalization, with at least six distinct tissue types contributing material that is combined with sperm in an ejaculate. Although studies of whole ejaculates have been undertaken in some species, we lack a comprehensive picture of the specific proteins produced by different accessory tissues. Here, we perform proteomic investigations of six regions of the male reproductive tract in mice—seminal vesicles, anterior prostate, dorsolateral prostate, ventral prostate, bulbourethral gland, and bulbourethral diverticulum. We identify 766 proteins that could be mapped to 506 unique genes and compare them with a high-quality human seminal fluid data set. We find that Gene Ontology functions of seminal proteins are largely conserved between mice and humans. By placing these data in an evolutionary framework, we show that seminal vesicle proteins have experienced a significantly higher rate of nonsynonymous substitution compared with the genome, which could be the result of adaptive evolution. In contrast, proteins from the other five tissues showed significantly lower nonsynonymous substitution, revealing a previously unappreciated level of evolutionary constraint acting on the majority of male reproductive proteins.